ANALISIS DAYA SAING DAN DAMPAK KEBIJAKAN JAGUNG HIBRIDA DI DESA TALINDUKA KECAMATAN DANGIA KABUPATEN KOLAKA TIMUR - Putri; Nur, Muhammad Nur; Hartati; Aryati (Agrisurya, 2023)
The research objective was to determine the impact of government regulations on the demand for hybrid corn production in Talinduka Village, Dangia District, East Kolaka Regency.  This research was conducted in June 2022 with a total sample of 36 hybrid corn farmers using random sampling method. Sampling was done simply randomly, where all farmers have the same opportunity to be used as respondents. Data analysis techniques combine a narrative research style with a quantitative approach. The Policy Analysis Matrix (PAM) is used to examine how government policies affect the competitiveness of hybrid corn cultivation in Talinduka Village. The results showed that hybrid corn farming was very competitive where both private profits and social benefits were positive. This study also found that the comparative advantage and competitive advantage were seen from the DRCR value of 0.12 (<1) and PCR of 0.32 (<1), indicating that the region has a strong competitive advantage in hybrid maize cultivation.  Although government regulations have affected the ability of the Talinduka Village Hybrid Corn farmers to compete, this has not effectively protected the farmers because the Talinduka Village hybrid maize farmers receive fewer personal benefits than they would have received without government policies.